2008
DOI: 10.2147/vhrm.s993
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome proliferator-activated receptor-γ agonists and diabetes: Current evidence and future perspectives

Abstract: Abstract:Since their initial availability in 1997, the thiazolidinediones (TZDs) have become one of the most commonly prescribed classes of medications for type 2 diabetes. In addition to glucose control, the TZDs have a number of pleiotropic effects on myriad traditional and non-traditional risk factors for diabetes. TZDs may benefi t cardiovascular parameters, such as lipids, blood pressure, infl ammatory biomarkers, endothelial function and fi brinolytic state. In this review, we summarise the experimental,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(38 citation statements)
references
References 84 publications
0
31
0
Order By: Relevance
“…The yolk cells in zebrafish were shown to process lipids during development, and the exposure of zebrafish with a PPARγ antagonist changed the composition of the lipid profile of 5DPF larvae with increasing/decreasing effects on different lipid species, mainly phospholipids [50]. Studies in mice and clinical trials of PPARγ agonists as thiazolidinediones showed that PPARγ had a role on the distribution of body fat [51]. As a response to TZD (thiazolidinedione) treatment, the metabolically more harmful adipose tissue (the visceral adipose tissue) decreased, while subcutaneous adipose tissue increased, which in part explained the beneficial effects of TZD.…”
Section: Discussionmentioning
confidence: 99%
“…The yolk cells in zebrafish were shown to process lipids during development, and the exposure of zebrafish with a PPARγ antagonist changed the composition of the lipid profile of 5DPF larvae with increasing/decreasing effects on different lipid species, mainly phospholipids [50]. Studies in mice and clinical trials of PPARγ agonists as thiazolidinediones showed that PPARγ had a role on the distribution of body fat [51]. As a response to TZD (thiazolidinedione) treatment, the metabolically more harmful adipose tissue (the visceral adipose tissue) decreased, while subcutaneous adipose tissue increased, which in part explained the beneficial effects of TZD.…”
Section: Discussionmentioning
confidence: 99%
“…PPARγ agonists (e.g. pioglitazone) have been widely used in the treatment of diabetes mellitus [17] and the prevention of macrovascular events and the development of diabetes in patients with insulin resistance [18].…”
Section: Introductionmentioning
confidence: 99%
“…PPARG plays a predominant role in adipogenesis and maintains the sensitivity to insulin. Due to this, TZD class of drugs that act as PPARG agonist has been widely used as insulin-sensitizing drugs in type-2 diabetes (Chiarelli and Di Marzio, 2008). PPAR can have a diverse role in physiology as evident from the fact that different isoforms have differential tissue expression and elicit different responses (Janani and Ranjitha Kumari, 2015).…”
Section: Introductionmentioning
confidence: 99%